Xchannel Radio Jakarta's Strategy In Increasing Listener Loyalty Through Social Media - Agnestia, Citra; Anggraeni, Dian; Herlina, Herlina (Jurnal Ilmu Sosial Mamangan, 2024)
Radio has been very close to the community from the colonial era to the current digital age. However, the popularity of radio in this digital era has declined due to the emergence of various digital platforms that have displaced radio. Many radios have been unable to maintain their popularity and have ended up failing to compete in the current era. However, Xchannel Radio has managed to survive in this digital era by entering social media platforms such as Instagram. In this research, the researcher is interested in discussing how Xchannel Radio's strategy to enhance listener loyalty through social media. The approach used in this research is a descriptive qualitative approach. The methods employed are interviews, observations, and documentation, with the research technique being a case study. The type of data used includes exposition, and data analysis using qualitative data analysis. The results of this study indicate that the strategy used by Xchannel Radio to increase listener loyalty through social media involves entering social media and becoming a part of it. However, Xchannel Radio maintains a distinct impression from other music platforms and treats its listeners as friends.